2013
DOI: 10.1007/s11920-013-0358-3
|View full text |Cite
|
Sign up to set email alerts
|

Neural, Psychophysiological, and Behavioral Markers of Fear Processing in PTSD: A Review of the Literature

Abstract: As presently defined, post-traumatic stress disorder (PTSD) is an amalgam of symptoms falling into: re-experiencing of the trauma, avoidance of reminders of it, emotional numbing and hyperarousal. PTSD has a well-known proximate cause, commonly occurring after a life-threatening event that induces a response of intense fear, horror, and helplessness. Much of the advancement in understanding of the neurobiology of PTSD has emerged from conceptualizing the disorder as one that involves substantial dysfunction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 64 publications
(51 reference statements)
2
50
0
Order By: Relevance
“…Estimates for victims of rape are up to 80% (Javidi and Yadollahie 2012). Because PTSD is viewed as a disorder of the brain’s fear system (Shvil et al 2013), experimental fear conditioning is one of our most important research models related to PTSD as well as to other anxiety disorders. However, it is important to note that although fear conditioning plays a role in psychopathology, it normally underlies adaptive behavior that extinguishes when the fear-inducing stimulus is withdrawn (Breslau et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates for victims of rape are up to 80% (Javidi and Yadollahie 2012). Because PTSD is viewed as a disorder of the brain’s fear system (Shvil et al 2013), experimental fear conditioning is one of our most important research models related to PTSD as well as to other anxiety disorders. However, it is important to note that although fear conditioning plays a role in psychopathology, it normally underlies adaptive behavior that extinguishes when the fear-inducing stimulus is withdrawn (Breslau et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…PTSD is viewed as a disorder of the brain’s fear system (Shvil et al 2013). As such, experimental fear conditioning is one of our most important research models related to PTSD, as well as of other anxiety disorders (Davis 1990; Davis 1992 ; Foa et al 1992; Grillon et al 1996; Shalev et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Fear conditioning and extinction paradigms have proven extremely valuable in revealing underlying circuitries of anxiety pathology and for understanding the development and maintenance of PTSD (Pitman et al, 2012; Shvil, Rusch, Sullivan, & Neria, 2013). Recent evidence specifically associates PTSD with impaired capacity to recall extinction memory, demonstrated by increased skin conductance levels to previously extinguished conditioned stimuli (Milad, Pitman, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent comparative study across subjects reporting primarily PTSD, general anxiety, or depression symptoms, extinction deficits were only observed in subjects with PTSD (Acheson et al 2015b), suggesting that poor extinction is specifically related to trauma-related symptoms as opposed to general symptoms of low mood or ruminative anxiety. PTSD patients also exhibit functional and structural abnormalities in the fear extinction network including the hippocampus, amygdala, and frontal cortex [for review see Acheson et al (2012a), Shvil et al (2013)]. During extinction learning, PTSD is associated with reduced activation of the ventral medial prefrontal cortex and increased activation of the amygdala and dorsal anterior cingulate, suggesting reduced inhibitory modulation by cortical inputs to fear circuits (Shvil et al 2013).…”
Section: Do Ptsd Patients Exhibit Changes In Fear Extinctionmentioning
confidence: 99%
“…PTSD patients also exhibit functional and structural abnormalities in the fear extinction network including the hippocampus, amygdala, and frontal cortex [for review see Acheson et al (2012a), Shvil et al (2013)]. During extinction learning, PTSD is associated with reduced activation of the ventral medial prefrontal cortex and increased activation of the amygdala and dorsal anterior cingulate, suggesting reduced inhibitory modulation by cortical inputs to fear circuits (Shvil et al 2013). Twin studies suggest that poor extinction observed in PTSD is associated with symptom state, rather than a vulnerability trait for PTSD (but see Lommen et al 2013;Milad et al 2008), suggesting it could play a role in maintenance of PTSD symptoms once they emerge.…”
Section: Do Ptsd Patients Exhibit Changes In Fear Extinctionmentioning
confidence: 99%